A comparison between primary debulking surgery and primary chemotherapy in patients with advanced ovarian cancer: a retrospective study - Mohamed Esmat; Mohamed Ashour (Al-Azhar Assiut Medical Journal, 2018)
Background Early detection of ovarian cancer is troublesome owing to the obscurity of conspicuous clinical symptoms. Hence, 75% of patients with ovarian cancer usually present and are diagnosed at an advanced stage (International Federation of Gynecology and Obstetrics stage IIIC or IV). Objective This study was conducted to evaluate the surgical and oncological consequences of patients with advanced ovarian cancer (International Federation of Gynecology and Obstetrics III/IV) who were subjected to either primary debulking surgery (PDS) followed by chemotherapy or primary chemotherapy (PC) followed by interval debulking surgery (IDS). Patients and methods We retrospectively reviewed the medical files of patients with advanced ovarian cancer who were admitted to the Surgical Oncology Unit, Bab-Elsharya University Hospital, between September 2008 and October 2013. Patients subjected to PDS succeeded by six cycles of chemotherapy, 6 weeks prior PDS, were enrolled in the PDS group, whereas patients subjected to three cycles of PC followed by IDS were enrolled in the PC-IDS group. Results This study recruited 104 consecutive patients with advanced ovarian cancer who received either PDS (52 participants) or PC-IDS (52 participants). The median overall survival time was 29.3 and 30.1 months in PDS and PC-IDS groups, respectively. Moreover, no significant difference was observed between patients subordinated to PDS (18.2%) and PC-IDS (15.41%) regarding overall survival rates (log-rank test, P=0.273). Conclusion PC-IDS can be an alternative procedure in the management of advanced ovarian cancer owing to not only similar survival rates but also with the advantages relative to PDS regarding postoperative morbidities.